Connectedness in the Context of Patient-Provider Relationships: A Concept Analysis - Phillips-Salimi, Celeste R. (2011)
AIM: This paper is a report of an analysis of the concept of connectedness. BACKGROUND: Previous attempts to conceptualize patient–provider relationships were limited in explaining how such relationships are fostered and maintained, and how they influence patient outcomes. Connectedness is a concept that may provide insights into the advantages of patient–provider relationships; however, the usefulness of this concept in health care is limited by its conceptual ambiguity. Although connectedness is widely used to describe other social relationships, little consistency exists among its definitions and measures. DATA SOURCES: Sources identified through CINAHL, OVID, PubMed, and PsychINFO databases, as well as references lists of selected articles, between 1983 and 2010. REVIEW METHODS: A hybrid concept analysis approach was used, involving a combination of traditional concept analysis strategies that included: describing historical conceptualizations, identifying attributes, critiquing existing definitions, examining boundaries, and identifying antecedents and consequences. RESULTS: Using five distinct historical perspectives, seven attributes of connectedness were identified: intimacy, sense of belonging, caring, empathy, respect, trust, and reciprocity. A broad definition of connectedness, which can be used in the context of patient–provider relationships, was developed. A preliminary theoretical framework of connectedness was derived from the identified antecedents, attributes, and consequences. CONCLUSION: Research efforts to advance the concept of connectedness in patient–provider relationships have been hampered by a lack of conceptual clarity. This concept analysis offers a clearer understanding of connectedness, provides recommendations for future research, and suggests practice implications.